Changing parental depression and sensitivity: Randomized clinical trial of ABC's effectiveness in the community. (August 2021) - Perrone, Laura; Imrisek, Steven D.; Dash, Allison; Rodriguez, Melanie; Monticciolo, Erasma; Bernard, Kristin
Abstract: Attachment and Biobehavioral Catch-up (ABC) demonstrates efficacy in improving parent and child outcomes, with preliminary evidence for effectiveness in community settings. The objective of this study was to assess the effectiveness of a community-based ABC implementation in improving parent outcomes as well as to examine potential mediators and moderators of intervention effectiveness. Two hundred parents and their 5- to 21-month-old infants recruited from an urban community were randomly assigned to receive ABC or be placed on a waitlist. The majority of participants had a minority racial or ethnic background. Before intervention, parents completed questionnaires about sociodemographic risk and adverse childhood experiences. At both baseline and follow-up, parents reported depression symptoms and were video-recorded interacting with their infant, which was coded for sensitivity. The ABC intervention predicted significant increases in parental sensitivity and, among parents who completed the intervention, significant decreases in depression symptoms. Changes in parental depression symptoms did not significantly mediate the intervention effects on sensitivity. Risk variables did not moderate the intervention effects. The results indicate that ABC shows promise for improving parent outcomes in community settings, supporting dissemination.